2018
DOI: 10.1111/1475-6773.13058
|View full text |Cite
|
Sign up to set email alerts
|

Response error and the Medicaid undercount in the current population survey

Abstract: Objective To measure the Medicaid undercount and analyze response error in the 2007‐2011 Current Population Survey Annual Social and Economic Supplement (CPS ASEC). Data Sources/Study Setting Medicaid Statistical Information System (MSIS) 2006‐2010 enrollment data linked to the 2007‐2011 CPS ASEC person records. Study Design By linking individuals across datasets, we analyze false‐negative error and false‐positive error in reports of Medicaid enrollment. We use regression analysis to identify factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…We offer these results-on CPS-specific questions (general source of coverage and program name), the more widely used post-ACA PPS items, and algorithm-based coverage type reporting accuracy ratesas baseline findings for several reasons. First, while there is a wellestablished literature on reporting accuracy for Medicaid, 2,18,[21][22][23][24][25][26] for other coverage types the literature is far more scant. 19 2,18,19,[21][22][23][24][25][26][27] We also note that the algorithm is simplistic and does not leverage all the data points available in the CPS, nor does it utilize observed reporting patterns across data points among actual enrollees.…”
Section: Discussionmentioning
confidence: 99%
“…We offer these results-on CPS-specific questions (general source of coverage and program name), the more widely used post-ACA PPS items, and algorithm-based coverage type reporting accuracy ratesas baseline findings for several reasons. First, while there is a wellestablished literature on reporting accuracy for Medicaid, 2,18,[21][22][23][24][25][26] for other coverage types the literature is far more scant. 19 2,18,19,[21][22][23][24][25][26][27] We also note that the algorithm is simplistic and does not leverage all the data points available in the CPS, nor does it utilize observed reporting patterns across data points among actual enrollees.…”
Section: Discussionmentioning
confidence: 99%
“…However, administrative counts are used as the official tally of program enrollment and used by the federal statistical system and academic researchers to benchmark survey estimates. [15][16][17][18][19]…”
Section: Data Limitationsmentioning
confidence: 99%
“…More recent work on the CPS, prior to the redesign of the health insurance module in 2014, found that the undercount declined from 32 percent in 2001 to 22 percent in 2010. 17 Chattopadhya and Bindman 24 found that the undercount increased in the California sample of the CPS from 1995 to 1999. They attributed the increase to the proliferation of Medicaid managed care which they argued was easily confused with private coverage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations